UPAYA PENGENALAN PAKAIAN ADAT INDONESIA PADA ANAK SEKOLAH DASAR, MENGGUNAKAN AUGMENTED REALITY PADA BOOK DESIGN - CLARA RIYANTI TERESA; BERTI ALIA BAHADURI; SANDY RISMANTOJO (Serat Rupa: Journal of Design, 2017)
Indonesia is an archipelago with a variety of cultures, one of which is the traditional clothing. According to the Indonesian elementary school curriculum in 2013, the contents about Indonesian Traditional Clothing are taught in grade four elementary school. The writer gathered the fact that only a few children who are interested in Indonesian Traditional Clothing because the learning media is very minimal and unattractive. The improvements of technology especially on smartphone can be the best way to apply the more attractive education for children. This design aims to introduce Indonesian Traditional Clothing in interesting and innovative ways to improve children’s interest. It also uses attractive media in books and takes advantage of the children’s smartphone to teach the material of Indonesian Traditional Clothing. Through this design, the book still serves as the main medium of learning; to attract children to learn about Indonesia clothing can be delivered effectively. The method used to collect data are literatures study and interview, then experiments in drawing the traditional costumes using the preferable illustration style. The final stag is to create an interactive book that integrates with smartphone applications to convey information about Indonesian Traditional Clothing children. The book is completed with interesting visual and peek-a-boo interactive that can be connected to a smartphone application as a supporting medium with audio features. Through this book design, children can get to know and be interested in Indonesian Traditional Clothing, so it can be known from the early age. Keywords: book; children; Indonesian traditional clothing; interactive